DAMPAK KEBIJAKAN PERATURAN DAERAH PROVINSI RIAU NOMOR 2 TAHUN 2011 TENTANG RETRIBUSI PELAYANAN TERA/TERA ULANG (Studi di Kota Pekanbaru Tahun 2012 - 2014) - Ibnu Mulkan; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
To protect the public interest in sectors of industry and trade is necessary to guarantee the correctness of measurement as well as their order and legal certainty in the use of units of measure, unit standards, measurement methods of measuring tools, measure, weigh and equipment (UTTP). To the Regional Government of Riau Province Riau Provincial Regulation imposes No. 2 of 2011 on Service Fees Tera / Tera Repeat with the aim of improving regional levies by as many people in the truth and protect the measuring instrument, measure, scales, and equipment, provide consumer protection, improve the smooth trade and realizing healthy competition.The purpose of this research is to provide an overview of Policy Impact Tera / Tera Repeat in Riau province, especially in Pekanbaru. To achieve the objectives of this study, the type of research is qualitative descriptive that is to give a clear picture of the issues under study, interpret and explain the data systematically. The research approach is qualitative, by interviewing the informant that contains questions related to this study.The results showed that the policy applies Riau Provincial Regulation No. 2 of 2011 on Service Fees Tera / Tera Repeat, is to provide protection to the people in terms of their correctness measuring instrument, measure, weigh, and equipment (UTTP), and collect fees with a maximum the amount to increase the regional revenue (PAD). An implementation of Tera Policies / Tera Repeat is not optimal due to limited calibration expert, inadequate technical equipment, and the geographic location makes the implementation of Tera / Tera Repeat has not run optimally.Keywords: Impact, Tera Policies/Tera Repeat